Efeitos avaliação da poluição atmosférica de Vitória-ES: caracterização físico-químico e citogenotóxicos em plantas - Galter, Iasmini Nicoli (2022)
Itapemirim river is considered one of the most important water resources of the Espírito Santo. Considering the ecological and socio-economic importance of this water resource, the concern about water quality is crucial, which makes necessary water assessment with approaches that integrate abiotic aspects to toxicogenetics assays. This study aimed to evaluate the water quality of Itapemirim river, through analysis of abiotic and toxicogenetics aspects, using as a test organism A. cepa, O. niloticus, and mammalian cell culture. Therefore, we defined four sampling stations along the Itapemirim river, to collect water samples during two periods: high precipitation and dry spell. From the samples were evaluated conductivity (S / cm) water temperature (° C), dissolved oxygen (mg / L) and pH, as well as quantified metals concentration. For Allium cepa assay were performed root growth test and cytogenetic analysis. Micronucleus test and comet assay were made with O. niloticus specimens. MTT test and comet assay were performed with CHO-K1 cells. Most abiotic variables evaluated showed waters from two campaigns are according to CONAMA Resolution No. 357/2005, as well as most metals. However, Al and Cu levels were above in the water regarding the legislation. Based on the results, it was verified that the compounds present in the waters of these river have the phytotoxic, genotoxic and mutagenic potential for the two in vivo and in vitro test organisms. The most significant results were obtained from the RI 03 sample, probably because it is related to the fact that the station is near to urban area of Cachoeiro Itapemirim / ES. It was also noted that the two campaigns conducted showed negative effect on bioassays performed. The data in this study indicate that water quality of Itapemirim river is committed and alert to the risk that domestic and industrial wastewater discharges have on water bodies, especially because of the complex chemical constitution presented.